2022
DOI: 10.1126/science.abn2688
|View full text |Cite
|
Sign up to set email alerts
|

Broad anti–SARS-CoV-2 antibody immunity induced by heterologous ChAdOx1/mRNA-1273 vaccination

Abstract: Heterologous prime-boost immunization strategies have the potential to augment COVID-19 vaccine efficacy. We longitudinally profiled severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S)–specific serological and memory B cell (MBC) responses in individuals who received either homologous (ChAdOx1:ChAdOx1) or heterologous (ChAdOx1:mRNA-1273) prime-boost vaccination. Heterologous messenger RNA (mRNA) booster immunization induced higher serum neutralizing antibody and MBC responses against SARS-Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 36 publications
10
59
0
Order By: Relevance
“…Whether this reflects increased T help due to responses to the N protein or a difference in vector dosing with group 2 hamsters receiving double the dose of the AdC-S vector is unknown. As expected, and reported by others, VNAs cross-reacted albeit with significantly reduced activity against viral variants of concern [45][46][47].…”
Section: Discussionsupporting
confidence: 90%
“…Whether this reflects increased T help due to responses to the N protein or a difference in vector dosing with group 2 hamsters receiving double the dose of the AdC-S vector is unknown. As expected, and reported by others, VNAs cross-reacted albeit with significantly reduced activity against viral variants of concern [45][46][47].…”
Section: Discussionsupporting
confidence: 90%
“… 27 , 33 , 34 Booster‐dose vaccination of either homologous and/or heterologous vaccines was safe and produces significant immunogenicity against Covid‐19 variants. 35 , 36 , 37 , 38 However, a preliminary study from Israel has shown that although the level of antibodies increased with the fourth booster shot of BNT162b2 mRNA vaccine, they were insufficient to prevent Omicron infection. 39 …”
Section: Resultsmentioning
confidence: 99%
“… 88 , 93 , 96 , 99 101 , 116 Moreover, administering three doses of BNT162b2 and mRNA-1273 vaccines increased effectiveness against Omicron to ~65% and 72%, respectively, compared with unvaccinated mice. 107 Interestingly, heterologous booster vaccination has the potential to induce adequate neutralizing efficacy, 89 , 92 , 117 , 118 which is important for augmenting the protection provided by some vaccines with insufficient neutralizing antibodies. For instance, heterologous booster vaccination with aerosolized Ad5-nCoV, a representative of adenovirus-vectored vaccines, generated greater neutralizing antibody responses against the Omicron variant than that generated by homologous booster vaccination with CoronaVac, 119 which provided an effective alternative in response to the Omicron.…”
Section: Immune Evasionmentioning
confidence: 99%